Individual differences in distraction by motion predicted by neural activity in MT/V5 - Lechak, Jennifer R.; Leber, Andrew B. (Frontiers in Human Neuroscience, 2012)
Individuals differ substantially in their susceptibility to distraction by irrelevant visual information. Previous research has uncovered how individual variability in the goal-driven component of attentional control influences distraction, yet it remains unknown whether other sources of variability between individuals also predict distraction. In this fMRI study, we showed that an individual’s inherent sensitivity to passively viewed visual motion predicts his/her susceptibility to distraction by motion. Bilateral MT/V5 was localized in participants during passive viewing of moving stimuli, affording a baseline measure of motion sensitivity. Next, participants performed a visual search task with an irrelevant motion singleton distractor, and both behavioral and neural indices of distraction were recorded. Results revealed that both of these indices were predicted by the independent index of motion sensitivity. An additional analysis of moment-to-moment fluctuations in distraction within individuals revealed that distraction could be predicted by pretrial fMRI activity in several brain regions, including MT+, which likely reflected the observer’s momentary propensity to process motion. Together, these results shed light on how variability in factors other than goal-driven processing, both within and between individuals, affects attentional control and one’s perception of the visual world.